Answer:
![f^(-1)(x)=(x+3)/(2)](https://img.qammunity.org/2022/formulas/mathematics/college/sw87ju4eicvdo227frfk6z3mu3guzht6ii.png)
Explanation:
The inverse of an equation is when you switch the x-value with the y-value. The y-value is equal to f(x). So, your work will look something like this. Note the changes in bold.
f(x) = 2x - 3
f(x) = y
y = 2x - 3
x = 2y -3
x + 3 = 2y
= y
y =
(here, I'm just switching it so the y-value is on the left to make it easier to read)
y = f(x)
(x) is the notation for inverse f(x)
So, the final equation would be written as
![f^(-1)(x)=(x+3)/(2)](https://img.qammunity.org/2022/formulas/mathematics/college/sw87ju4eicvdo227frfk6z3mu3guzht6ii.png)